Parenting stress in childhood leukaemia. - Zarina AL,; Radhiyah R,; Hamidah A,; Syed Zulkifli Syed Zakaria,; Rahman Jamal, (Penerbit UKM, 2012)
Parenting stress is the stress level experienced within the role of a parent (Hoekstra-Weebers et al. 1998). The source of stressors is variable and dependent on the phase of disease and chemotherapy (Sawyer et al. 2000). Failure to cope with these stressors may in turn affect the child’s emotional and social adjustment towards the diagnosis of cancer in addition to poor medical treatment adherence behaviour (Sawyer et al. 1993). The objectives of this study are to determine the level of parenting stress, the risk factors contributing to high parenting stress, and the coping mechanisms used to handle the stress. This single centred, cross-sectional study was done amongst 117 parents at the Paediatric Haematology and Oncology Unit, Universiti Kebangsaan Malaysia Medical Centre (UKMMC) over two years duration. Self-administered questionnaires comprising the Parenting Stress Index/Short Form (PSI/SF) and Coping Inventory for Stressful Situation (CISS) were distributed to parents of children who were 12 years old and below. The mean total parenting stress score amongst parents of children diagnosed with acute leukaemia was 91.5±21.1(95% CI). A total of 27.3% of parents experienced a high total parenting stress score (defined as total PSI score ≥ 75th centile, ie ≥ 103). Task-oriented coping mechanism was used by the majority of parents. Emotion-oriented coping mechanism was the only identifiable risk factor for high parenting stress score following multiple logistic regression analysis. A parent who used emotion-oriented coping mechanism was 7.1 times (95% Confidence Interval 1.2 to 41.4) more likely to have a high parenting stress score compared to a parent who used other coping mechanisms. By identifying these at-risk parents, appropriate counselling and psychological support may be offered early to alleviate the stress as well as assist in the coping and adjustment mechanisms of these parents.